Fatores que interferem no processo ensino aprendizagem do aluno em estágio supervisionado da UFMA - Silva, Elza Lima (2003)
Analysis of the intervening factors in the íearning process of the students of the graduation course in nursing, apprenticeship Discipline Supervised at UFMA’s Surgical Center. It has for general aim the description of the situation lived by the students in the field of the Apprenticeship. The methodological approach is analytic- descriptive and design belongs to study of ease, having as unit of analysis the Academic Hospital. They took part in the study 31 students. They got to the conciusion that the Surgical Center is a naturally stressing context, which there is lack of facilitative ritual of the obstruction of the students with the team of the Service, which there is power game of the surgeon as boss of the team, which maturity fault to the students and, which despite initial probiems the students finished the Apprenticeship with certain satisfaction degree.